MicroRNA-194 Inhibits Lipopolysaccharide-Induced Inflammatory Response in Nucleus Pulposus Cells of the Intervertebral Disc by Targeting TNF Receptor-Associated Factor 6 (TRAF6) - Kong, Lili (Med Sci Monit, 2018)
BACKGROUND: The dramatic increase of intervertebral disc degeneration (IDD) is considered to be a major cause of discogenic low back pain. The current study focused on the regulatory function of microRNA-194 (miR-194) on lipopolysaccharide (LPS)-induced inflammatory response in nucleus pulposus (NP) cells. MATERIAL/METHODS: LPS was used to treat NP cells to induce inflammatory responses. MiRNA and gene expression were detected by quantitative PCR. Proteins and protein expression levels were detected by Western blot and ELISA kit. Dual luciferase reporter assay was applied to identify the correlation between an miR-194- and TNF receptor-associated factor 6 (TRAF6) and to test NF-κB activity. RESULTS: MiR-194 expression was reduced in LPS-induced NP cells. Both miR-194 overexpression and miR-194 inhibitor could regulate extracellular matrix (ECM) genes expression (Aggrecan and collagen II), MMP3, MMP13, ADAMTS4, and ADAMTS5, as well as inflammatory cytokines-associated genes (TNF-α, IL-1, IL-6, PGE2). Through a further study of the molecular mechanism, miR-194 was proved to be involved in the regulation of TRAF6 and its downstream signal molecule, nuclear factor-kappa B (NF-κB). CONCLUSIONS: Finding of our study suggest that miR-194 can inhibit LPS-induced inflammatory response in NP cells of the intervertebral disc (IVD) by targeting TRAF6, which may contribute development of IDD biological therapy.